THE INFLUENCE OF ACTIVITIES USING IMPLICIT MULTIPLE INTELLIGENCES TOWARDS STUDENTS' EFFECTIVE EFL LEARNING - Pertiwi, Rini Anggun (2014)
This study is aimed at exploring whether teaching stages in MI based approach could help students improve their ability in learning English as a foreign language as well as to find out students' responses towards the approach to their learning ability in the English language. A descriptive research design embracing case study characteristics was employed (Nunan, 1992; Cresswell, 2012). The data were obtained from classroom observation (observation and video recording of the learning process through multiple intelligence based approach), and interview with students. Students' activities in the classroom were analyzed in order to identify the students' personal unique combination of eight intelligences and figure out a wide range of intelligence-oriented activities which facilitate students' effective learning (Armstrong, 2009; Dean, 2000). This study revealed that, to some extent, MI based approach was helpful to develop students' ability to learn English effectively and figured out that teachers often not wholly involved all the eight intelligences into learning activity. Keywords: Multiple Intelligences, learning strategies, effective learning.